Does bank competition reduce cost of credit? Cross-country evidence from Europe - Zuzana Fungáčová; Anastasiya Shamshur; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
Despite the extensive debate on the effects of bank competition, only a handful of single-country studies deal with the impact of bank competition on the cost of credit. We contribute to the literature by investigating the impact of bank competition on the cost of credit in a cross-country setting. Using a panel of firms from 20 European countries covering the period 2001–2011, we consider a broad set of measures of bank competition, including two structural measures (Herfindahl-Hirschman index and CR5), and two non-structural indicators (Lerner index and H-statistic). We find that bank competition increases the cost of credit and observe that the positive influence of bank competition is stronger for smaller companies. Our findings accord with the information hypothesis, whereby a lack of competition incentivizes banks to invest in soft information and conversely increased competition raises the cost of credit. This positive impact of bank competition is however influenced by the institutional and economic framework, as well as by the crisis.
URN:NBN:fi:bof-201604071075
Keywords: G21; L11; 330